The development of scientific thinking through John Dewey's method of reflective understanding of knowledge - Loayza Maturrano, Edward Faustino (2023)
An unresolved problem in the formation of investigative competence is how to develop scientific thinking in the future researcher, since procedures, strategies and methods are required to guide the process of knowledge generation. Thus, the purpose of this theoretical article is to conceive a way to develop scientific thinking through John Dewey's method of reflective understanding of knowledge. The interpretative-propositive theoretical study is complemented with a survey applied to university students, who manifest the effectiveness of the Dewey method in the formation of scientific thought. In the results and discussion, the five phases of Dewey's reflective thinking are explained: Problem recognition, establishment of provisional hypotheses, investigation of the current situation of the problem, hypothesis revision and hypothesis testing. Likewise, the understanding stage, the prediction stage and the analysis stage are analyzed to develop ideas. It is concluded that if students are systematically educated in the phases and stages of Dewey's reflective understanding of knowledge, they will be able to effectively develop scientific thinking.